Specific transcriptional initiation in vitro on murine type C retrovirus promoters. - Ostrowski, M C (1981)
We have investigated the ability of molecularly cloned murine type C retroviral DNA to direct accurate initiation of RNA synthesis when added to cell-free extracts. Two different cloned proviruses were used. The first was derived from an integrated molecule of AKR murine leukemia virus and contains adjacent host information. The origin of the second was an unintegrated permuted copy of Harvey murine sarcoma virus. We found that the leukemia virus cloned provirus, as predicted by structural considerations, contained two functional RNA polymerase II promoters located in the U3 region present at either end of the molecule. These promoters initiate transcription at equal rates in vitro. We also found that the permuted sarcoma virus clone contained an RNA polymerase II promoter in the U3 region. Removal of viral sequences 49 bases upstream of the in vitro sarcoma virus initiation site by restriction cleavage results in loss of specific transcription, indicating a role for this information in in vitro promotion. The 5' ends of in vitro and in vivo viral RNA were compared by nuclease mapping techniques and found to be identical. Based on this evidence, we conclude that murine retroviral genomes contain sufficient information to initiate transcription independent of any host information in vitro and that these viral promoters are probably also active in vivo. In addition to the promoter in U3, Harvey murine sarcoma virus contains a second promoter in vitro that initiates near the 5' boundary of the transformation-specific (src) region of the virus. Initiation by this promoter was insensitive to low levels of alpha-amanitin, and the RNA transcript could be terminated to yield a 340-nucleotide product.